2016
DOI: 10.1186/s12879-016-1968-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and effect of pre-treatment drug resistance on the virological response to antiretroviral treatment initiated in HIV-infected children – a EuroCoord-CHAIN-EPPICC joint project

Abstract: BackgroundFew studies have evaluated the impact of pre-treatment drug resistance (PDR) on response to combination antiretroviral treatment (cART) in children. The objective of this joint EuroCoord-CHAIN-EPPICC/PENTA project was to assess the prevalence of PDR mutations and their association with virological outcome in the first year of cART in children.MethodsHIV-infected children <18 years initiating cART between 1998 and 2008 were included if having at least one genotypic resistance test prior to cART initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
6
2
Order By: Relevance
“…However, previous studied have reported conflicting results. Several African and multinational studies reported a positive association between PDR and virologic suppression while other studies and in contrast to other African and Asian studies reported the lack of any association between PDR and virological suppression [39,40]. Our study showed that, after adjusting for other baseline factors, presence of any PDR was associated with reduced rates of virological suppression.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…However, previous studied have reported conflicting results. Several African and multinational studies reported a positive association between PDR and virologic suppression while other studies and in contrast to other African and Asian studies reported the lack of any association between PDR and virological suppression [39,40]. Our study showed that, after adjusting for other baseline factors, presence of any PDR was associated with reduced rates of virological suppression.…”
Section: Discussioncontrasting
confidence: 66%
“…The impact of PDR on virologic outcomes among newly-diagnosed HIV infected children is not well established in resource-limited settings [22,[36][37][38][39]. In theory, PDR could compromise the efficacy of first-line cART regimens, thereby reducing rates of virological suppression and increasing subsequent rates of virological treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences showed that different predictors affect treatment failure. The most common predictors are age [7, 10–14], gender [10–12], being orphan [15], time from ART initiation [15], poor adherence to ART failure [10, 11, 1618] [19], nevirapine (NVP)-based regimen [13, 20], drug side-effects, drug toxicity [10, 11, 16, 17], nutritional status [11], pretreatment CD4 count [1, 10, 11, 13, 14, 16, 19, 21], WHO clinical stage [911, 16, 19, 21] and tuberculosis co-infection [9, 19]. A previous study [22] does not address important predictor like repeated measurement for CD4 which this includes.…”
Section: Introductionmentioning
confidence: 99%
“… 39 ATHENA collaborates with other research groups and observational cohorts in western Europe, the USA and Canada. Data sharing and collaboration has taken place or is ongoing with the Collaboration of Observational HIV Epidemiological Research Europe (COHERE), 40 EuroSIDA, 41 the European Pregnancy and Paediatric HIV Cohort Collaboration (EPPICC) 42 within the Paediatric European Network for the Treatment of AIDS (PENTA), the European Coordinating Committee for the Integration of Ongoing Coordination Actions Related to Clinical and Epidemiological HIV Research (EuroCoord); A Collaboration on HIV-2 infection (ACHI E V 2E ) 43 ; Antiretroviral Therapy Cohort Collaboration (ART-CC) 44 ; Data collection on Adverse events of anti-HIV Drugs (D:A:D) 45 ; HIV Cohorts Analysed Using Structural Approaches to Longitudinal data (HIV-CAUSAL) Collaboration 46 ; Bridging the Evolution and Epidemiology of HIV in Europe (BEEHIVE) 47 ; HIV Resistance Response Database Initiative (RDI) 48 49 ; and International epidemiology Databases to Evaluate AIDS (IeDEA). 50 …”
Section: Strengths and Limitationsmentioning
confidence: 99%